Nashville. The complete second season [videorecording (DVD)]. - Britton, Connie; Panettiere, Hayden; Jackson, Jonathan, 1982-; Esten, Charles, 1965-; Close, Eric; Carmack, Chris, 1980- (ABC Studios, 2014)
Rayna Jaymes and Juliette Barnes are at the top of their game, but in Nashville, the higher you rise, the farther you fall. In the aftermath of her mother's death, Juliette is poised to shine brighter than ever, until a sordid scandal threatens to destroy her. Meanwhile, after Rayna nearly loses her life (and her voice) in a horrific accident, she bounces back with her own record label and a new man. But can she still electrify audiences without Deacon by her side?